EVALUASI RISIKO TERJADINYA DISFUNGSI SEKSUAL PASIEN KANKER KOLOREKTAL DENGAN STOMA: A SYSTEMATIC REVIEW - zuliawati Zuliawati; Rostiodertina Girsang; Friska Ernita Sitorus (Jurnal Penelitian Keperawatan Medik, 2020)
Objective: Stoma is a surgical procedure commonly used for the treatment of colorectal cancer patients, this will affect the patient's sexuality problems. This research study with qualitative and quantitative research designs published between 2008 to 2018 in English articles. Methods: PubMed, EBSCO, and Google Scholar, are sought to evaluate the risk of sexual dysfunction in colorectal cancer patients with stoma. Results: Research that has been explored in nine consists of mixed methods case control, case control retrospective study, systematic review, phenomenology study, multiple logistic regression, prospective descriptive study, longitudinal study, cross sectional design, descriptive comparison study. Most of the findings of the study show that sexual dysfunction is a problem of concern. Conclusions: evaluating sexual dysfunction problems in colorectal cancer patients with stoma, are the basic essence of nursing intervention. Health care professionals must be more aware of the problems of risk factors for sexual dysfunction experienced by patients after making stoma, so that services and treatments performed are more optimal.